Internal Marketing and Brand Promise Delivery of Indian Public Sector Banks : A Causal Relationship Analysis - Thomas, Baby; Rodrigues, Ana Paula (Indian Journal of Marketing, 2020)
Substantial contribution of the Indian banking industry to national GDP and its potential to generate millions of jobs convey the significance of how qualitative its workforce should be in terms of delivering its brand promises to its customers. Positive influence of internal marketing practices on organizational performance has been empirically proven and established. However, brand promise delivery as a research construct is not broadly investigated, especially in the context of internal marketing practices of commercial banks. A multi-dimensional model or path analysis was used to find out the causal relationship among the model-constructs and its variables using the methodology of quantitative questionnaire survey collecting data from 300 employees from leading five Indian public sector banks. The results of the study confirmed that internal marketing practices had a significant effect on brand promise delivery of public sector banks through the mediation effect of its job-related attitudes of organizational commitment and organizational citizenship behaviour. The managerial or practical implications of the study are that the policy makers of the Indian public sector banks should recognize the significance of getting their employee behaviour aligned with their marketing objectives by benchmarking internal marketing practices and ensuring that the brand promises are duly delivered to their key stakeholders, the customers.